Fiscal policy effectiveness and the golden rule of public finance - Irem Zeyneloglu (Central Bank Review (CBR), 2018)
The present paper uses a dynamic stochastic general equilibrium (DSGE) framework with imperfect competition and nominal rigidities in order to analyze the impact of two different fiscal rules on the effectiveness of fiscal policy. The first rule is called the golden rule of public finance which allows an upward shift in the share of public investment in total public spending but restricts the use of public debt for investment purposes alone. The second rule does not alter the allocation of public spending among investment and consumption but allows public consumption to be financed by public debt. The numerical results show that a fiscal expansion under the golden rule leads to a higher increase in output while maintaining a low level of public debt compared to the second rule. Moreover, the difference between the output responses under the two fiscal rules increase in the medium run implying that the benefits of a golden rule-based fiscal policy are higher especially in the medium run.
Keywords: 330; Fiscal policy; Golden rule of public finance; DSGE models